Application of medical equipment procurement data mining using the Apriori method - Phindika, Phindika; Handrianto, Yopi; Sukmana, Sulaeman Hadi (Sinkron : jurnal dan penelitian teknik informatika, 2021)
The procurement of an item in an agency is an activity that is commonly carried out, including in a hospital, particularly the procurement of medical equipment. The procurement of medical equipment at Pengayoman Cipinang Hospital, Jakarta currently still uses the conventional method where the process is still using the manual method, namely by relying on disposable physical items as the main resource and seems to use many procedures that require a long working time. The influx of medical equipment in very large numbers can cause many risks, such as the amount of money it costs to store medical devices and also being vulnerable to the risk of theft. The conditions mentioned above can affect the quality of health services provided by the hospital to patients who should be well preserved. One of the data processing algorithms that is often used in the data mining process is the A algorithm. The benefit is to find trends between one item and another, where more and more medical equipment appears to be used as a reference in the hospital policy process in ensuring the availability of this medical equipment when needed so that the procurement process can always be fulfilled. Based on the results of the research conducted, it was found that the medical equipment that had the most demand was Surgical Ear Loop Masks 3 (58.33%), Non-Sterile Gloves Size M (58.33%), and Surgical Tie-On 3 PLY Masks (100%)